First results from the IllustrisTNG simulations: radio haloes and magnetic fields - Marinacci, Federico; Springel, Volker; Pillepich, Annalisa; Pakmor, Rüdiger; Weinberger, Rainer (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. We introduce the IllustrisTNG project, a new suite of cosmological magnetohydrodynamical simulations performed with the moving-mesh code arepo employ
Gesehen am 25.01.2019